Mechanisms of toxic action of copper and copper nanoparticles in two Amazon fish species: Dwarf cichlid (Apistogramma agassizii) and cardinal tetra (Paracheirodon axelrodi) - Braz-Mota, Susana; Campos, Derek F.; MacCormack, Tyson J.; Duarte, Rafael M. [UNESP]; Val, Adalberto L.; Almeida-Val, Vera M.F. (Elsevier, 2018)
Copper oxide nanoparticles (nCuO) are widely used in boat antifouling paints and are released into the environment, potentially inducing toxicity to aquatic organisms. The present study aimed to understand the effects of nCuO and dissolved copper (Cu) on two ornamental Amazon fish species: dwarf cichlid (Apistogramma agassizii) and cardinal tetra (Paracheirodon axelrodi). Fish were exposed to 50% of the LC50 for nCuO (dwarf cichlid 58.31 μg L−1 and cardinal tetra 69.6 μg L−1) and Cu (dwarf cichlid 20 μg L−1 and cardinal tetra 22.9 μg L−1) for 24, 48, 72 and 96 h. Following exposure, aerobic metabolic rate (ṀO2), gill osmoregulatory physiology and mitochondrial function, oxidative stress markers, and morphological damage were evaluated. Our results revealed species specificity in metabolic stress responses. An increase of ṀO2 was noted in cardinal tetra exposed to Cu, but not nCuO, whereas ṀO2 in dwarf cichlid showed little change with either treatment. In contrast, mitochondria from dwarf cichlid exhibited increased proton leak and a resulting decrease in respiratory control ratios in response to nCuO and Cu exposure. This uncoupling was directly related to an increase in reactive oxygen species (ROS) levels. Our findings reveal different metabolic responses between these two species in response to nCuO and Cu, which are probably caused by the differences between species natural histories, indicating that different mechanisms of toxic action of the contaminants are associated to differential osmoregulatory strategies among species.
Keywords: CuO nanoparticles; Metabolic rate; Mitochondria respiration; Ornamental Amazon fishes; Oxidative stress; Reactive oxygen species